Tendências emergentes na interconexão entre doenças periodontais e neurodegenerativas: uma análise bibliométrica dos 100 artigos mais citados - SANTOS, Anderson Cesar Costa (2025)
This bibliometric analysis aims to identify and analyze the most cited articles on the relationship between Periodontal Diseases and Neurodegenerative Diseases. A search in the Web of Science Core Collection was conducted by two independent examiners. Selected articles addressed the correlation between oral health conditions and neurological diseases. After selecting the most cited articles, information such as authorship, article title, journal name, publication year, citation count, corresponding author's country and continent, keywords, and study design were extracted. Notably, our research revealed a significant prevalence of periodontal disease bacteria activity in dementia progression, especially Alzheimer's. Emphasizing the importance of such studies, it provides insights to enhance global dementia awareness, given the expected surge in Alzheimer's prevalence and associated public expenditures in the next decade. The majority of studies underscore oral hygiene and periodontal health maintenance as practices ensuring systemic health and potentially delaying cognitive decline.